Conceptualizing alternate regimes in a large floodplain-river ecosystem: Water clarity, invasive fish, and floodplain vegetation. (15th June 2020) - Bouska, Kristen L.; Houser, Jeffrey N.; De Jager, Nathan R.; Drake, Deanne C.; Collins, Scott F.; Gibson-Reinemer, Daniel K.; Thomsen, Meredith A.
Abstract: Regime shifts - persistent changes in the structure and function of an ecosystem - are well-documented for some ecosystems and have informed research and management of these ecosystems. In floodplain-river ecosystems, there is growing interest from restoration practitioners in ecological resilience, yet regime shifts remain poorly understood in these ecosystems. To understand how regime shifts may apply to floodplain-river ecosystems, we synthesize our understanding of ecosystem dynamics using an alternate regimes conceptual framework. We present three plausible sets of alternate regimes relevant to natural resource management interests within the Upper Mississippi River and Illinois River. These alternate regimes include: 1) a clear water and abundant vegetation regime vs. a turbid water and sparse vegetation regime in lentic, off-channel areas, 2) a diverse native fish community regime vs. an invasive-dominated fish community regime, and 3) a regime characterized by a diverse and dynamic mosaic of floodplain vegetation types vs. one characterized as a persistent invasive wet meadow monoculture. For each set of potential alternate regimes, we review available literature to synthesize known or hypothesized feedback mechanisms that reinforce regimes, controlling variables that drive regime transitions, and current restoration pathways. Our conceptual models provide preliminary support for the existence of alternate regimes in floodplain-river ecosystems. Quantitatively testing hypotheses contained within the conceptual model are important next steps in evaluating the model. Ultimately, the synthesis and evaluation of alternate regimes can inform the utility of resilience concepts in restoration and management on the Upper Mississippi River and Illinois River and improve our understanding of ecosystem dynamics in other large, heavily managed floodplain-river ecosystems. Highlights: Alternate regime concepts have rarely been applied to river ecosystems. We assess three potential sets of alternate regimes for a large river. Long-term changes in the Upper Mississippi River are consistent with regime shifts. Altered disturbance dynamics and invasive species coincide with observed changes. Conceptual models of alternate regimes provide insights into river ecosystems.